SEJARAH DAN NALAR HUMANISME ISLAM PERSPEKTIF MOHAMMED ARKOUN (1928-2010) - H. Zuhri (UIN Sunan Kalijaga Yogyakarta, 2015)
Muhammad Arkoun is a contemporary Muslim philosopher. Among all his original ideas, his endeavor to reform the Islamic religiosity to become the modem and hu• mane religiosity, seems distinguished in his works. This effort will be projected by Zuhri in this writing. It appears in this task, as it explores in this writing, Arkoun proposed a lexiconographicalmethod or lexiconology,the compilation and the implant of ideas. The lexiconographical method is a method that tries to portrait the use and words choosing in the text so that it demonstrates universal meanings that surpass the space and time. While by the compilation's method, Arkoun performed regrouping ideas of the sentences within the text. The power of this method is situated in the unity of the idea that built in that text. Whereas by the implant of ideas, Arkoun provided thinking thematic branch to be implanted to a stem and a root of idea that already in the text so that creates a unity in one perspective that emerge contextual understanding which have thinking roots and solid argumentation. From the side ofmaterial ideas, by that reading's method, Arkoun tried to redefine the relation between the aware• ness, religion, rationality,culture, history and human/humanity.